2020
DOI: 10.1016/j.ijid.2020.01.036
|View full text |Cite
|
Sign up to set email alerts
|

Statin use and risk of tuberculosis: a systemic review of observational studies

Abstract: Statin intake may be linked with a lower risk of several infectious diseases, including tuberculosis, which is an important cause of mortality worldwide. The aim of this study was to investigate the definite impacts of statins on the risk of tuberculosis (TB) in diabetic patients and in the general population. Methods: Four databases were thoroughly searched from inception up to July 2019. Articles in any language were included if they assessed and clarified statin intake, presented the risk of TB in diabetes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…Statins are commonly used agents used to reduce serum lipids and systemic inflammation to improve outcomes in patients with a history of or at risk for ASCVD. Prior systematic reviews have shown that statin use reduces TB incidence, both in patients with DM and in the general population 28 , 29 . Preclinical studies in macrophage and mouse models have demonstrated that statins enhance autophagy and phagosome maturation 24 , increase the proportion of NK cells, and increase secretion of the pro-inflammatory cytokines IL-1β and IL-12p70, thereby reducing the lung bacillary burden in M. tuberculosis -infected mice 24 , 49 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Statins are commonly used agents used to reduce serum lipids and systemic inflammation to improve outcomes in patients with a history of or at risk for ASCVD. Prior systematic reviews have shown that statin use reduces TB incidence, both in patients with DM and in the general population 28 , 29 . Preclinical studies in macrophage and mouse models have demonstrated that statins enhance autophagy and phagosome maturation 24 , increase the proportion of NK cells, and increase secretion of the pro-inflammatory cytokines IL-1β and IL-12p70, thereby reducing the lung bacillary burden in M. tuberculosis -infected mice 24 , 49 .…”
Section: Discussionmentioning
confidence: 99%
“…As adjunctive therapy, statins improve sterilizing activities of the first-line anti-tubercular regimen in murine models 24 27 . Though systematic reviews have shown that statin use reduces the incidence of active TB 28 , 29 , there is no clinical evidence on whether statins have salutary effects in TB patients after adjusting for confounding factors 30 .…”
Section: Introductionmentioning
confidence: 99%
“…Statins are commonly used agents used to reduce serum lipids and systemic in ammation in patients with a history of or at risk for ASCVD. Prior systematic reviews have shown that statin use reduces TB incidence both in patients with DM and in the general population 23,24 . Preclinical studies in macrophage and mouse models have demonstrated that statins enhance autophagy and phagosome maturation 19 , increase the proportion of NK cells, and increase secretion of the pro-in ammatory cytokines IL-1β and IL-12p70, thereby reducing the lung bacillary burden in M. tuberculosis-infected mice 19,42 .…”
Section: Discussionmentioning
confidence: 99%
“…As adjunctive therapy, statins improve sterilizing activities of the rst-line anti-tubercular regimen in murine models [19][20][21][22] . Though systematic reviews have shown that statin use reduces the incidence of active TB 23,24 , there is no clinical evidence on whether statins have salutary effects in TB patients after adjusting for confounding factors 25 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their cholesterol-lowering properties, β-Hydroxy β-methylglutaryl-CoA (HMG-CoA) reductase inhibitors (statins) have been shown to have broad anti-inflammatory and immunomodulatory properties (22,23), and their use has been associated with significantly decreased risk of TB (24). Statins have been shown to have antimicrobial and immunomodulatory activity in mouse models of infection against intracellular pathogens, including Salmonella enterica and Chlamydia pneumoniae.…”
Section: Statins As Adjunctive Hdt For Tbmentioning
confidence: 99%